PELATIHAN PENYUSUNAN LAPORAN KEUANGAN PADA MAHASISWA UNIVERSITAS ISLAM DARUL ULUM LAMONGAN - Have Zulkarnaen; Martha Laila Arisandra; Rifky Ardhana Kisno Saputra (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2022)
The era of the industrial revolution brought a huge impact on the company's lines of business in various parts of the world. This resulted in the development of an increasingly complex and rapid accounting. The process of making financial reports from the process of switching to an integrated computerized system. To harmonize graduate competencies and skills that can be applied in general with the development of increasingly sophisticated accounting technology, activities are carried out using Microsoft Excel applications in the preparation of financial reports. The Microsoft office application is more specific, the Microsoft Excel application was chosen because it combines basic accounting skills, computer applications that are commonly used and an adequate understanding of the English language in accordance with global competency needs.